Detecting the elusive Scottish wildcat Felis silvestris silvestris using camera trapping. Issue 2 (7th May 2014) - Kilshaw, Kerry; Johnson, Paul J.; Kitchener, Andrew C.; Macdonald, David W.
Abstract: Population monitoring is important for conservation management but difficult to achieve for rare, cryptic species. Reliable information about the Critically Endangered Scottish wildcat Felis silvestris silvestris is lacking because of difficulties in morphological and genetic identification, resulting from extensive hybridization with feral domestic cats Felis catus . We carried out camera-trap surveys in the Cairngorms National Park, UK, to examine the feasibility of camera trapping, combined with a pelage identification method, to monitor Scottish wildcats. Camera trapping detected individually identifiable wildcats. Of 13 individual wild-living cats, four scored as wildcats based on pelage characters and the rest were wildcat × domestic cat hybrids. Spatially explicit capture–recapture density estimation methods generated a density of wild-living cats (wildcats and hybrids) of 68.17 ± SE 9.47 per 100 km 2 . The impact of reducing trapping-grid size, camera-trap numbers and survey length on density estimates was investigated using spatially explicit capture–recapture models. Our findings indicate camera trapping is more effective for monitoring wildcats than other methods currently used and capture success could be increased by using bait, placing camera stations ⩽ 1.5 km apart, increasing the number of camera stations, and surveying for 60–70 days. This study shows that camera trapping is effective for confirming the presence of the wildcat in potential target areas for conservation management.